VARICOSE VEINS IN MALE WEAVERS; AN EPIDEMIOLOGICAL STUDY - D.Parvizpour (Tehran University of Medical Sciences, 1982)
The prevalence of varicose veins was studied in 1742 male weavers in Iran by completing a specially designed questionnaire and medical examination. To show the effect of occupation on the prevalence of the disease, similar study was conducted on a group of 1661 food- processing workers. The over- all prevalence of the disease in the weavers (26.12%) was significantly higher than the similar rate (5.90%) in the other group. A direct relationship between the prevalence of the disease and age was observed in both groups; however, the increase was more significant among the weavers. A direct relationship was also seen between the length of employment and the prevalence of the disease in the weavers only. Comparison of the severity of disease in the two groups indicates that weavers not only had a higher prevalence rate, but had more severe forms too. In conclusion, it may be said that varicose veins could be a health problem in the weavers and might be substantially reduced by preventive measures.